The impact of human rights organisations in prisoners rights advocacy in Zimbabwe : a case study of the Zimbabwe Human Rights Commission (ZHRC) - Boozai, Richard (Midlands State University, 2020)
The study seeks to analyze the human rights advocacy for prisoners by human rights organizations in the context of Zimbabwe Human Rights Commission .It majors on the impact of human rights organizations in line with ZHRC’s decision to engage in such advocacy. It analyzes the strategic tools and plans implored by humanitarian organizations to fight for human rights particularly related to prisoners .The research address the gap in the literature by assessing the existence of human rights violations in prisons and the commitment of human rights organizations to counter the ill-practices through advocacy strategies .Adding on, the research seeks to arrive at a point it assess the need of strategic planning for advocacy. It also assesses the interventions by human rights organizations, the problem identification, investigations work done by the human rights organizations as well as the strategic plan and the strategy for impact. It will also be a fact finding mission why the human rights organizations chose to engage in such work and how strategically they engage in such work, delivering what results .More to that theories were the support base of the thesis. Also both qualitative and quantitative research methods were used to gather information with the use of secondary and primary sources, having with qualitative research more widely used than the later. The researcher made use of questionnaires and interviews in gathering data from a selected population sample. The target population comprised of the officers from ZHRC, Zim-Rights, Prisoners and People from the society, being the general public from Bulawayo and Harare. About 53 questionnaires were administered. The researcher were necessary had to use the native language thus shona and Ndebele to assist in the interpretation of questions. The data gathered from the field was presented by the use of tables, bar graphs and pie-charts. Also the researcher had to analyze the data collected and presenting it in summary. The data gathered shows that human rights organization’s mandate of human rights advocacy is affected by poor strategic planning and that the human rights organizations are less responsive to the humanitarian needs of prisoners. As a result the researcher had to give recommendations on what has to be done to redress humanitarian responsiveness and proper strategic planning of human rights organizations.